Probiotic–Vaccine Synergy in Fish Aquaculture: Exploring Microbiome-Immune Interactions for Enhanced Vaccine Efficacy - Muhammad Tayyab; Waqar Islam; Waqas Waqas; Yueling Zhang (Biology)
The rapid expansion of aquaculture is vital for global food security, yet it faces persistent threats from disease outbreaks, vaccine inefficacy, and antibiotic overuse, all of which undermine sustainability. Conventional vaccines often fail to induce robust mucosal immunity, spurring interest in probiotics as adjuvants to enhance immunogenicity. Probiotics such as Bacillus subtilis and Lactobacillus casei modulate fish microbiomes, fortify mucosal barriers, and activate innate immune responses via mechanisms including Toll-like receptor signaling and cytokine production. These actions prime the host environment for prolonged adaptive immunity, improving antigen uptake and pathogen clearance. Experimental advances—such as Bacillus subtilis-engineered spores increasing survival rates to 86% in Vibrio anguillarum-challenged European seabass—demonstrate the potential of this synergy. Innovations in delivery systems, including chitosan–alginate microcapsules and synbiotic formulations, further address oral vaccine degradation, enhancing practicality. Probiotics also suppress pathogens while enriching beneficial gut taxa, amplifying mucosal IgA and systemic IgM responses. However, challenges such as strain-specific variability, environmental dependencies, and unresolved ecological risks persist. Optimizing host-specific probiotics and advancing multi-omics research is critical to unlocking this synergy fully. Integrating probiotic mechanisms with vaccine design offers a pathway toward antibiotic-free aquaculture, aligning with One Health principles. Realizing this vision demands interdisciplinary collaboration to standardize protocols, validate field efficacy, and align policies with ecological sustainability. Probiotic–vaccine strategies represent not merely a scientific advance but an essential evolution for resilient, ecologically balanced aquaculture systems.